(3JcfhdhLjG GdYed aj GdefXeI Hjf GdfXQjI h GdJWHjb (B/s - (3GdfYjej, YOfGf JGjg PjGHs ((3YeGf(B: s (3OGQ LdjS GdReGf(B, s, 2011)
(3GdebUhO HGdJcfhdhLjG, QhGO GdacQ GdGOGQj h GdJcfhdhLjG, GdOQGSGJ GdegJeI HbjGS CKQ GdJcfRdRLjG, JcfhdhLjG GdYed h ehGUaGJ GdCaQGO, GdYdGbI Hjf JcfhdhLjG GdYed h Gdgjcd GdJfXjej, GdYdGbI Hjf JcfhdhLjG GdYed h GdaGYdjIs
(3bGeI GdLOGhd U(B.221 (3HHdjhZQGajG(B: (3U(B.211-217s
Keywords: (3EOGQI GdCYeGds; (3GdJcfhdhLjGs; (3GdYeds; (3GdYed h GdYeGds